biochemical attributes and establishment of tree seedlings in soil after urochloa decumbens cultivation in soil with deposition of iron mining residues - Ribeiro Junior, Alexandre Carvalho; Silva, Aline Oliveira; Batista, Éder Rodrigues; Naves, Filipe Sales; Pinto, Flávio Araújo; Santos, Jessé Valentim dos; Barbosa, Marisângela Viana; Alvarenga, Ingrid Fernanda Santana; Carneiro, Marco Aurélio Carbone (CERNE, 2021)
abstract background: the recovery of areas impacted by mining activities is a major challenge and requires knowledge of how the biological and biochemical processes of the soil as well as the establishment of plant species are affected by mining residue. in this work, the influence of deposition of iron mining mud and tailings on soil biochemical attributes and the initial development of tree seedlings was studied in a simulated event in the greenhouse. pots (n = 27) with natural soil (2.0 kg) received deposition (280 ml) of iron mining mud or tailings and by three-month was cultivated with urochloa decumbens. at the end of this period, part of the pots was sampled and the soil biochemical activities were evaluated. then tree seedlings (schinus terebinthifolius and eremanthus incanus) were planted and cultivated for a year, when then shoot (sdw) and roots (rdw) dry weight were evaluated. results: deposition of iron mining mud and tailings did not affect microbial biomass carbon or basal soil respiration, however both conditions reduced (p < 0.05) β-glucosidase activities by up to 30%, and the easy extractable glomalin by about 19%. in addition, the mud deposition reduced (p < 0.05) the sdw and rdw of s. terebinthifolius by about 21% and 24%, respectively. nevertheless, uruchloa decumbens and eremanthus incanus had no variation in dry weight production between treatments, so they have good ability to grow settle in soil affected by mining residue. conclusion: this study shows that the sequential planting of u. decumbens and e. incanus can be an alternative for use in environments with deposition of iron mining tailings.